ORGANISASI MAPALUS DALAM PELAKSANAAN PEMBANGUNAN DI DESA KALEOSAN - KOMBAITAN, YESICHA; POSUMAH, JOHNNY HANNY; TAMPI, GUSTAAF BUDDY (Sam Ratulangi University, 2019)
The mapalus system in implementing development in the village has begun to disappear. Andthe main cause is all because of technological developments so that the people who have started to forget themapalus culture that has been valid in the village has become a tradition in the village. The purpose of thisstudy is to find out how mapalus organizations are in implementing development in the village. This studyuses descriptive qualitative research methods. Data collection techniques used are observation, interviews anddata collection with documents. To see how the mapalus organization is carrying out development in thevillage of Kaleosan. The researcher uses three indicators, namely: Planning and setting goals, providingservices and monitoring from the government. Based on the results of this study stated that the role of thecommunity and even the mapalus organization in the village in the implementation of development in thevillage is still very lacking because the community that along with technological development has begun toforget the habits of mapalus. mapalus in development. It can be concluded that the mapalus organization inthe implementation of development in Kaleosan village is still not good.Keywords: Mapalus ,Organization, Village Development